2016
DOI: 10.1590/abd1806-4841.20164476
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of health-related quality of life and adherence to treatment with calcipotriol-betamethasone dipropionate gel in patients with psoriasis vulgaris

Abstract: BACKGROUNDPsoriasis is a common, chronic, recurrent, immune-mediated disorder of the skin and joints. It can have a significant negative impact on the physical, emotional and psychosocial wellbeing of affected patients.OBJECTIVESTo measure improvement in health-related QoL (HRQoL) in Greek patients with psoriasis vulgaris after a month of treatment with calcipotriol-betamethasone dipropionate gel; and evaluate adherence to treatment parameters.METHODSThe study included 394 psoriasis vulgaris patients from 16 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…Psoriasis is associated with impaired quality of life (QoL) to a degree comparable with that in diseases such as malignancy, heart disease and diabetes . Studies have shown that QoL improves after successful treatment of psoriasis with topical applications …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriasis is associated with impaired quality of life (QoL) to a degree comparable with that in diseases such as malignancy, heart disease and diabetes . Studies have shown that QoL improves after successful treatment of psoriasis with topical applications …”
Section: Resultsmentioning
confidence: 99%
“…28 Studies have shown that QoL improves after successful treatment of psoriasis with topical applications. 29,30 Assessment of severity Assessment of disease severity is the cornerstone of psoriatic management and many options are available for this purpose. They vary from generic (e.g.…”
Section: Clinical Features and Comorbiditiesmentioning
confidence: 99%
“…Plaque, erythrodermic, pustular, inverse and guttate psoriasis are the diverse subtypes of psoriasis, according to the onset of the disease. Plaque psoriasis, also known as psoriasis vulgaris, is the most common clinical subtype, affecting about 90% of patients [ 2 , 3 ]. The lesions are well-defined papulosquamous scales characterized by the focal formation of erythematous, raised plaques that constantly shed scales derived from excessive growth of skin epithelial cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol levels tend to drop at night, which may play a role in nighttime exacerbation of pruritic symptoms . Although topical glucocorticoids exert antiinflammatory rather than antipruritic effects, they have been shown to improve sleep quality in children with nocturnal pruritus secondary to AD and in adults with nocturnal itching secondary to psoriasis …”
Section: Topical Therapiesmentioning
confidence: 99%